A Study on Circular Economy Transition in the Fashion Industry Through Business Model Innovation - Agrawal, Suyash (Digital Repository of Theses, 2024)
This study examines the role of circular startups in supporting the circular economy (CE) transition in the fashion industry through their innovative business models (BMs). CE has emerged as a potential alternative model to the current linear fashion. The literature on business model innovation (BMI) has focused on key stages of the BMI process, its implications, and challenges but lacks in defining a strategic framework required to construct and extend the CE network among the key supply chain players. This research study is based on a qualitative research method, utilizing a combination of individual interviews with the startups and survey questionnaires of the fashion value chain stakeholders. This approach allows for a comprehensive exploration of how these startups create and deliver value, emphasizing the development of unique product biographies essential in building business value propositions for their clients. Further contributing to the academic and practical understanding of circular business models (CBMs), the study explains the critical elements required to redefine BMs to support CE transition. The study presents a structured framework that articulates clear strategies for developing and expanding CE networks, facilitating synergistic collaborations between startups and established firms. The research found that CE-based startups in the fashion industry operationalize value creation and delivery within the seven elements of the BMI dimensions. Furthermore, the research findings highlight the efficacy of distinct networking strategies (Push, Pull, and Synced) followed by the startups in fostering and expanding CE-centric collaborations with established industry players. This strategic networking enhances the scalability of CE practices and integrates incumbent firms into the CE, marking a significant step toward sustainable fashion evolution. The research findings have valuable suggestions for existing fashion companies and entrants planning to collaborate with value chain players in developing and executing CBMs to support CE transition. Moreover, the networking strategies can offer actionable insights for practitioners seeking to navigate the complexities of sustainable transformation and can significantly boost the overall circularity goals. The policymakers could also use the insights to understand the long-term business potential of circular startups and support them in scaling up by enhancing market demand for their products and services.